Analisis Pengaruh Profitabilitas, Leverage, Kinerja Lingkungan dan Diversifikasi Gender Terhadap Kualitas Pengungkapan Lingkungan Pada Perusahaan Pertambangan di Indonesia - Amanda Oktariyani; Rachmawati, Yuni (Akuntansi dan Manajemen, 2021)
This paper investigates the effect of profitability, leverage, environmental performance and gender diversity on the quality of environmental disclosure by analyzing annual report of mining companies listed on Indonesia Stock Exchange during 2017 - 2019. Based on the purposive sampling method, 25 mining companies were selected. This study used panel data regression as the data analysis method. The result showed that profitability, leverage and gender diversity has not significant effect on quality of environmental disclosure, while environmental performance has positive and significant effect on quality of environmental disclosure. Thus, companies that has ISO 14001 certification tend to disclose information related to their responsibility to the environment more detail in annual reports.